Serum VEGF as a predictive marker of glycemic control and diabetic nephropathy in Chinese older adults with type 2 diabetes mellitus - Jiang, Yanyan; Li, Jianhua; Zhang, Juan; Chen, Sufang (Frontiers in Endocrinology, 2023)
Objectives Recent researches have demonstrated good correlation between vascular endothelial growth factor (VEGF) and diabetic nephropathy (DN); however, this relationship seems less clear-cut when VEGF was measured in blood samples. We tended to explore the possible association between serum VEGF and glycemic control and diabetic nephropathy severity in Chinese older adults with type 2 diabetes mellitus (T2DM). Materials and methods This study retrospectively enrolled 595 older T2DM adults at random. Participants were clinically grouped across the urine albumin-to-creatinine ratio (UACR) and the HbA1c tertiles by genders. Linear regressions were performed for the correlation of VEGF with HbA1c and UACR and binary logistic regressions for the odds of DN after adjusting for confounders. The receiver operating characteristic (ROC) curves were conducted for the predictive value of VEGF for DN. Results Both males and females with DN exhibited higher VEGF levels than non-DN (P < 0.001). Furthermore, a positive correlation of VEGF with UACR and HbA1c was presented regardless of adjusting confounding factors (P < 0.001). Serum VEGF level and fasting plasma glucose (FPG) were independent risk factors of DN in older adults of both genders (P < 0.05), while the risk prediction of DN by HbA1c only reflected in female patients (P < 0.05). The ROC curve of VEGF for DN had the area under curve (AUC) of 0.819 for males and 0.793 for females, indicating the clinical value of serum VEGF as a predictive biomarker. Conclusions Serum VEGF was strongly associated with UACR and HbA1c in both genders, and could be regarded as a predictive biomarker for glycemic control and diabetic nephropathy in older adults with T2DM.